THE CORRELATION OF READING INTEREST TO LEARNING OUTCOMES IN INDONESIAN LEARNER IN CLASS 5 of SDN 2 KARANG TANJUNG - Amanah, Laras Tazkiatul; Noviana, Rizki; Sofiah, Rodatus; Chamdani, Muhamad (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Reading interest is main factor to increase quality of student. The study activities in the school, highly reading interest of student is a something hoped for all people. This study aimed to determine the correlation of reading interest to learning outcomes in Indonesian language. This research focused in a something impact of reading interest to learning outcomes. The method used is descriptive method with technic questionnaire, observation, and interview. Research sample were students of class 5 numbering 20 people. Students read well fall into the category with a percentage 78,86 % while the study result in the category fairly with the average value of 58,9. Based on the correlation test with significance level α = 5% concluded there is a correlation between reading interest by learning outcomes in learning Indonesian fifth grade students of State Elementary School 2 Karang Tanjung with r table ≥ r count or 0.444 ≥ 0.029.